2015
DOI: 10.1002/esp.3702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human‐controlled hydrological regime on the source, transport, and flux of particulate organic carbon from the lower Huanghe (Yellow River)

Abstract: Evaluating the role of fluvial transfer of terrestrial organic carbon (OC) and subsequent burial in the global carbon cycle requires the sources and fluxes of fluvial OC to be assessed, which remains poorly constrained in the Huanghe (Yellow River). Here, we report the elemental, stable isotopic, and radiocarbon activity of particulate organic carbon (POC) sampled at the outlet of Huanghe in 2012–2013. We show that the Huanghe riverine POC can be explained by binary mixing of fossil (POCfossil) and non‐fossil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 97 publications
(241 reference statements)
5
41
0
Order By: Relevance
“…In the last 50 years the water level, due to water diversions, has dropped from 395 m to about 430 m below sea level. Hu et al (2015) analyzed the effect of hydrological regime managed by humans, on the source, transport, and flux of particulate organic carbon (POC) from the lower Huanghe (Yellow River, China). the reactivation of palaeochannels with subsidence, sinkholes, and landslides).…”
Section: The Anthropocene and Landscape Impactmentioning
confidence: 99%
“…In the last 50 years the water level, due to water diversions, has dropped from 395 m to about 430 m below sea level. Hu et al (2015) analyzed the effect of hydrological regime managed by humans, on the source, transport, and flux of particulate organic carbon (POC) from the lower Huanghe (Yellow River, China). the reactivation of palaeochannels with subsidence, sinkholes, and landslides).…”
Section: The Anthropocene and Landscape Impactmentioning
confidence: 99%
“…The estimated sediment discharge of the YR before 1970 was~1.08 Gt a À1 ; the discharge rapidly dropped to~0.15 Gt a À1 since 2000 due to reduced rainfall and artificial regulation of water and sediment discharge (Wang et al, 2006). Reduced freshwater and sediment discharge profoundly impacted the physical, biogeochemical and biological environment in the sea surrounding the delta of the YR. For example, Hu et al (2015) estimated that the particulate organic carbon discharge of the YR has decreased from 4. Su et al (2015) reported that the DIN concentrations near the YR mouth can reach up to 70 mM in the summer due to increased river input.…”
Section: Introductionmentioning
confidence: 99%
“…The percentages of POC in TSS at the four gauging stations varied from 0.6 to 6.1% with a mean value of 1.5 ± 0.6% for the whole Red River system and are similar to those of other rivers in Asia such as the Changjiang (1.16%) (Wu et al ), the Xijiang (1.2%) (Sun et al , ) , the Brahmaputra (0.50%), and the lower Yellow (0.75%) (Hu et al ), the Pearl River Delta (1.5–2.5%) (Ni et al , ) but are lower than in the Congo River (3.9–11.5%) (Coynel et al ).…”
Section: Discussionmentioning
confidence: 60%
“…() found a value of 1.0 in the Chanjiang River. Values from the Ganges River are even lower (0.3; Zhang et al ) , as in the Yellow River (0.08–0.16; Ran et al , ; Hu et al ) and Lanyang His Rivers (0.16; Kao and Liu ). The low values are due to the high riverine POC fluxes (70%) in this region.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation